ANALISIS MORFOLOGI DAN MORFOSTRUKTUR SERTA PENGARUHNYA TERHADAP BANJIR LUAPAN SUNGAI BENGAWAN SOLO HULU TENGAH - Suharjo -; Alif Noor Anna; Munawar Cholil; Rudiyanto - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Bengawan Solo river flow changes is estimated to occur about 2 or at least a million years ago. The image interpretation results obtained ancient Bengawan Solo river which has become a valley winding naturally potential to be flood-prone areas. The aim of this study is to asses the condition of morphology and morphostructure of River Bengawan Solo and the impact towards flood overflow. This research use survey method. Data analyzed by quantitative descriptive technique, assisted with GIS analysis. The results of this study are (a) the morphology of the present; positive skewed figures means that the material is the result of fluvial processes and susceptible to flood overflow. The direction of the flow is toward the North, to the North Coast of Java which is lower, (b) morphostructure at the present; Solo River water level leads to the North, but at a certain point, there are seen places which are uphill or places which are higher than before, which are must lower for a uphill or a higher place than before, which are should be lower. This cause the tilt to rise. Silting and erosion occurs at a certain point. Point 11-18 are the point that be the impact of streamlining river, so its flow getting swift. At some point (between 11-18) it seem very close the distance between the water height and the ground level, means that the water height close to the height of the surface, so that leaving it vulnerable to flood overflow. This condition is particularly worrying in case of rain with a large quantity of water that will be up and overflow onto the surface. At point 11, 13, and 16 clear to see that the river is very shallow if it is compared to other points.Keywords: morphology, morphostructure, Flood Overflow, Watersheed